2021
DOI: 10.3390/ijms22168641
|View full text |Cite
|
Sign up to set email alerts
|

Modulating the ERK1/2–MMP1 Axis through Corosolic Acid Inhibits Metastasis of Human Oral Squamous Cell Carcinoma Cells

Abstract: Corosolic acid (CA; 2α-hydroxyursolic acid) is a natural pentacyclic triterpenoid with antioxidant, antitumour and antimetastatic activities against various tumour cells during tumourigenesis. However, CA’s antitumour effect and functional roles on human oral squamous cell carcinoma (OSCC) cells are utterly unknown. In this study, our results demonstrated that CA significantly exerted an inhibitory effect on matrix metalloproteinase (MMP)1 expression, cell migration and invasion without influencing cell growth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 52 publications
0
13
0
Order By: Relevance
“…36 A research about human oral squamous cell carcinoma showed that MMP1 was expressed higher in tumor than normal tissue and its higher expression was positively correlated with a shorter overall survival rate. 37 Wang et al also found that MMP1 3'UTR can sponge miR-188-5p to facilitate the proliferation and migration of human oral squamous cell carcinoma. 38 Consistently, our results showed that MMP1 was significantly increased in HNSCCs and its high expression was positively correlated with poor prognosis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…36 A research about human oral squamous cell carcinoma showed that MMP1 was expressed higher in tumor than normal tissue and its higher expression was positively correlated with a shorter overall survival rate. 37 Wang et al also found that MMP1 3'UTR can sponge miR-188-5p to facilitate the proliferation and migration of human oral squamous cell carcinoma. 38 Consistently, our results showed that MMP1 was significantly increased in HNSCCs and its high expression was positively correlated with poor prognosis.…”
Section: Discussionmentioning
confidence: 99%
“…Lallemant et al reported that MMP1 shows high sensitivity and specificity for serving as a diagnostic marker in HNSCC 36 . A research about human oral squamous cell carcinoma showed that MMP1 was expressed higher in tumor than normal tissue and its higher expression was positively correlated with a shorter overall survival rate 37 . Wang et al also found that MMP1 3’UTR can sponge miR‐188‐5p to facilitate the proliferation and migration of human oral squamous cell carcinoma 38 .…”
Section: Discussionmentioning
confidence: 99%
“…The above analysis supported the role of PTPN2 in suppressing PDAC metastasis in vitro experiments. Therefore, we chose MMP‐1 (Matrix Metallopeptidase 1) as the target gene, because MMP‐1 has been reported to promote cancer metastasis in various cancer types 29–31 (Figure 4F). Besides, MMP‐1 belonged to the most enriched three GO terms in Figure 5D.…”
Section: Resultsmentioning
confidence: 99%
“…Also, GO-Biological Process analysis showed that the enriched genes were subjected to cell migration, such as extracellular structure organization, extracellular matrix organization, and positive regulation of cell adhesion (Figure 4C). Moreover, we carried out GSEA enrichment analysis (http://www.linkedomics.org/login.php) based on all the PDAC patients from TCGA databases, indicating that PTPN2 was inversely correlated with terms associated with cell invasion, including cell-cell adhesion and cell projection membrane (Figure 4D,E [29][30][31] (Figure 4F). Besides, MMP-1 belonged to the most enriched three GO terms in Figure 5D.…”
Section: Ptpn2 Depletion Induced the Accumulation Of Mmp-1 Thereby Pr...mentioning
confidence: 99%
“…Recently, our group found that bLF reversed the programing of epithelial-to- mesenchymal transition (EMT) to mesenchymal-to-epithelial transition (MET) in OSCC by decreasing the ERK signaling pathway, reducing the expression of TWIST, and improving membrane bound E-Cadherin [ 11 ]. Currently, evidence is accumulating that the ERK1/2/MMP-1 axis could inhibit metastasis of human oral squamous cells [ 45 ], and that knocking down of MMP-1 could suppress the PI3K/Akt/c-myc signaling pathway and EMT in colorectal cancer [ 46 ]. In addition, MMP-3 directly mediated EMT by upregulating TWIST, thereby disrupting E-cadherin expression [ 47 , 48 ].…”
Section: Discussionmentioning
confidence: 99%